EXPLORING THE HISTORICAL CONTEXT OF THE QUR'AN - Aufaqurrizqi, Fiqih; Thobroni, Ahmad Yusam (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
This study aims to conduct a comparative analysis of the Asbabun Nuzul works by Al-Wahidi and As-Suyuthi in understanding the historical context behind the revelation of Qur'anic verses. Al-Wahidi and As-Suyuthi are two prominent figures in the tradition of Qur'anic exegesis who have made significant contributions to the development of the science of Asbabun Nuzul. Using a descriptive-analytical approach, this article compares the methodology, structure, and relevance of these works in contemporary exegesis studies. The findings reveal that Al-Wahidi focuses more on concise and chronological narratives, whereas As-Suyuthi incorporates broader linguistic and historical analyses. This study concludes that both works complement each other in providing a comprehensive understanding of the background of Qur'anic verses.